The Importance of Emotional Intelligence and Social Learning in General Education Institutions - Bregadze, Maia (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
In the 21st century, alongside intellectual quotient characteristics, the concept of "emotional intelligence" (EQ) has gained significant prominence. Modern studies indicate that individuals with high IQs may possess notable talents, yet success often favors those with lower intellectual abilities due to their higher emotional intelligence.Emotional intell igence pertains to a person's interpersonal skill set, involving the ability to manage emotions and self-control, crucial for effective human relationship management within social contexts. Mainstream educational institutions primarily focus on imparting knowledge to students, emphasizing intellectual development, while the role of social and emotional learning is increasingly recognized as pivotal for future success. To what extent do modern schools incorporate approaches to foster student development in this regard? What specific components of social-emotional learning correlate with academic achievement? How is the national curriculum adapted to address these issues, and how effective are teachers' strategies in nurturing emotional intelligence? Various challenges and barriers may arise in the process of social-emotional learning. Therefore, examining specific case studies and comparing existing theoretical studies through empirical research, including in-depth interviews with experts in the field, becomes crucial to justifying the relevance of such studies. This small-scale study aims to highlight essential orientations in modern education and underscore the critical aspects of social-emotional education necessary for comprehensive student development.